APLIKASI TEKNOLOGI ELEKTROKOAGULASI PADA PENGOLAHAN LIMBAH INDUSTRI ELEKTROPLATING SEBAGAI UPAYA MENGHASILKAN PRODUKSI KERAJINAN LOGAM BERBASIS GREEN TECHNOLOGY - Aji Prasetyaningrum; Yudhy Dharmawan (Jurnal Riptek, 2018)
Chromium (VI) is one of the major metallic pollutants aside of arsenic, copper and nickel in plating industrial wastewater. Cr(VI) is one of toxic metal that cause serious threat to human health and the environment because its non-biodegradable. Among the technologies for removing these pollutants, electrocoagulation can be considered as an effective method.This method have some advantages such as less amount of produced sludge and high efficiency in removal of pollutants.This research intended to study the effects of type of electrode on the degree of Cr(VI) removal from wastewater of plating industry using electrocoagulation method.This laboratory research conducted with 3 types of electrode (aluminum, stainless and combination of both electrode). Synthetic chromium wastewater was prepared at the initial concentration of 100 mg L-1. The process was conducted at pH 3. The electricity current was setting at 3 Ampere. The variable of time of electrocoagulation at 1 and 2 hours. After performing the process on electrochemical cells, samples analyzed by the UV-Vis spectrophotometer regarding amount of Cr(VI) metals. The results showed that aluminium was the best performance electrode at variable 2 hours with   26% reduction of Cr(VI) metal content in waste water.